The Improved Hybrid Algorithm for the Atheer and Berry-Ravindran Algorithms - Atheer Akram Abdul Razzaq; Nur’Aini Abdul Rashid; Alaa Ahmed Abbood; Zurinahni Zainol (Institute of Advanced Engineering and Science, 2018)
Exact String matching considers is one of the important ways in solving the basic problems in computer science. This research proposed a hybrid exact string matching algorithm called E-Atheer. This algorithm depended on good features; searching and shifting techniques in the Atheer and Berry-Ravindran algorithms, respectively. The proposed algorithm showed better performance in number of attempts and character comparisons compared to the original and recent and standard algorithms. E-Atheer algorithm used several types of databases, which are DNA, Protein, XML, Pitch, English, and Source. The best performancein the number of attempts is when the algorithm is executed using the pitch dataset. The worst performance is when it is used with DNA dataset. The best and worst databases in the number of character comparisons with the E-Atheer algorithm are the Source and DNA databases, respectively.